CHARGE Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
A 12 month old male infant with the CHARGE syndrome (Coloboma, Heart defect, Atresia of the choana, Retarded growth and development, Genital hypoplasia, Ear anomalies or deafness) is reported from the Departments of Pediatrics and Neurology, Loyola University, Chicago.